Room temperature photon-magnon coupling in YIG- electric field coupled resonator system - Abhishek Maurya; Kuldeep Kumar Shrivastava; Sachin Verma; Rajeev Singh; Biswanath Bhoi (Chemical Physics Impact)
This study presents a planar hybrid system consisting of an electric-field-coupled resonator (ELCR) and yttrium iron garnet (YIG) film, designed to investigate the interaction between photons and magnons at room temperature. This hybrid system has been designed and simulated using the commercial electromagnetic full-wave simulator CST Microwave Studio. The phenomenon of anti-crossing between the photon mode of the ELCR and the magnon modes of the YIG was observed by analyzing the |S21|-versus-frequency spectrum under varying strengths of bias magnetic fields. We present a comprehensive theoretical framework that explains the observed anti-crossing effect resulting from photon-magnon coupling (PMC) and provide estimations for the strength of PMC (Δ). Additionally, the interaction between photons and magnons was manipulated through two distinct methods: by adjusting the thickness (tYIG) of the YIG film and by positioning the YIG films along the microstripline. For the ELCR (for tYIG = 25 μm), Δ comes to 58 MHz, while changing tYIG from 2 μm to 50 μm, enabling more precise control of the Δ parameter across the span of 17 MHz to 84 MHz. Similarly, the YIG positioning at a different location along the microstripline allowed manipulation of Δ from 5 to 50 MHz. The resultant PMC can be significantly tuned by 400% to 900% in a planar-geometry ELCR-YIG hybrid system. This research offers avenues for developing innovative hybrid systems that afford greater control over the magnitude of PMC in a planar configuration, representing a promising direction for future advancements in hybrid magnonic systems.